How to Train Evaluators of Adult Education Staff at a European Level? Towards the Design of a Pilot Curriculum in Edueval Project - Perla, Loredana; Vinci, Viviana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The evaluation of professionals involved in Adult Education staff has a crucial role in order to guarantee the quality of Adult Education (AE). EduEval is a project of the LLP Grundtvig Programme, coordinated by University of Milano-Bicocca, Italy (http://www.edueval.eu/), established with the main objective of redefining the professional profile of the evaluator of Adult Education staff. In this framework, six partners from five European countries work with a collaborative approach. The project offers a new methodology in the field of AE that arises from the importance of a cooperation between practitioners of the AE staff and academic researchers. The paper focuses on the pilot course designed by University of Bari to create a curriculum for the initial training of the professionals involved in the evaluation of AE staff.